A New Spectrophotometric Method for the Assay of Plant Phenolics - Mumtazuddin, S. (Asian Journal of Chemistry, 2016)
A new spectrophotometric method for the assay of total phenolics in plants is reported. Neutral ferric chloride solution has been used as a complexing agent. This is a simpler method than the earlier reported ones for the phenolics assay.